UNSUR-UNSUR ADMINISTRASI PENDIDIKAN DI MIS AL HAFZA ISLAMIC GLOBAL SCHOOL Abyena Hafza1, Afrida Juliani2, Putri Rizky3, Mursal Aziz4 - Hafza, Abyena; Juliani, Afrida; Rizky, Putri; Aziz, Mursal (Jurnal Media Informatika, 2024)
This research is entitled "Elements of Educational Administration at MIS Al-Hafza Islamic Global School". The implementation of an administrative system is one of the factors that influences the quality of education. By implementing educational administration, schools are more planned, directed and have clear goals so that the school implementation process is more effective and efficient. Therefore, the researcher raised the issue of administrative elements at MIS Al-Hafza Islamic Global School. In this research, researchers used qualitative research methodology with descriptive methods, namely by observation and interviews. The results of this research are that the elements of educational administration at MIS Al-Hafza Islamic Global School can be said to be good. Where in this institution there are elements of education administration, namely all school components such as the principal, deputies and coordinators as well as teachers. The most important part in something that makes the existence or existence of something is the administrative element. Education has 7 elements, namely educational programs, students, human resources, school buildings consisting of offices and classes, assistance services, and funds. The conclusion of this research is that the elements of educational administration at the MIS Al Hafza Islamic Global School school are said to be good because they meet the criteria for elements of education in general, where there are principals, treasurers, educators, TU staff, educational programs, students, human resources, the school building consists of offices and classrooms, this school is more focused and has clear goals because it fulfills these administrative elements.